Hubungan Pemakanan Sunnah Dengan Pembinaan Karektor Usahawan Berintegriti: (Relationship between Sunnah Nutrition and the Character Building of Entrepreneurs with Integrity) - Ab Rahim, Nik Mohd Zaim; Abd Razzak, Monika @ Munirah (Online Journal of Research in Islamic Studies, 2024)
This article discusses the relationship between Sunnah nutrition and the development of the character of entrepreneurs with integrity in Islamic entrepreneurship. Integrity, which encompasses honesty, trustworthiness, and transparency, is crucial in business. Sunnah nutrition, being balanced and healthy, plays a key role in shaping the character of entrepreneurs with integrity. It not only benefits physical and mental health but also fosters self-discipline in making ethical decisions. Proper dietary practices enhance energy, focus, and emotional well-being, while also teaching etiquette such as avoiding wastefulness and maintaining good relationships, which are essential in building entrepreneurs with integrity. This study employs content analysis methodology to assess the relationship between Sunnah nutrition and the development of the character of entrepreneurs with integrity. Through this approach, the article analyzes the Qur’anic texts, Hadiths, and previous studies related to Sunnah nutrition and integrity in entrepreneurship. The analysis results indicate that Sunnah nutrition not only benefits health but also forms the character of ethical, disciplined, and integral entrepreneurs, in alignment with the values embedded in Islamic teachings. In conclusion, Sunnah nutrition plays an important role in the formation of an entrepreneur's character with integrity, enabling them to fulfill their obligations and business affairs more effectively.